Islamic unit trust: investor’s perception towards it / Rohaya Azmi - Azmi, Rohaya (2011)
In turning Malaysia as a one stop centre for Islamic financial instruments, Shariah unit trust have become another important for issuers who seek the lowest cost and investors who search for the highest return that based on Shariah principles. The Shariah unit trust is the collective investments funds which offer investors the opportunity to invest in a diversified portfolio of Shariah compliant securities which are managed by professional manager accordance with the syariah committee or a Shariah adviser to ensure that their operations are in accordance with Shariah. The main objective of Islamic unit trust is to invest in a portfolio of halal permissible stocks which comply with the principles of the Shariah examples halal stocks will exclude companies involved in activities, product or services related to conventional banking, insurance and financial services, gambling alcoholic beverages and non halal food products. The return of Islamic unit trust must also avoid the incidence of riba or usury interest through the process of cleansing or purification by the removal of such amounts represents the interest element. As a focus on perception investors towards Islamic unit trust, a Shariah compliant unit trust involves three parties namely the investors/unit holders who invest the money in the fund. Akad is initiated between the investors and the manager. The manager been appointed by the investors to undertake the investment activities on behalf of them, the trustee who acts as the independent party to safeguard the investors assets of the fund and the operation of a Shariah compliant unit trust scheme is governed by a legal document called deed. It shows the rights and obligations of the manager, the rights and duties of the trustee and the rights of the unit holders. It also specifies in detail how the fund is to be operated and managed and how fees are to be charged. At all times, the investment of the fund would be restricted to securities/instruments that are allowed under Shariah and prohibited from investing in securities /instrument which do not comply with the Shariah principles. The investment portfolio of the Shariah fund comprises securities which have been classified as Shariah compliant by the SAC or bank Negara Malaysia. For securities not certified by the sac or bank Negara Malaysia, the status of the securities must be determined in accordance with the rulings issued by the Shariah panel.